2004
DOI: 10.1177/014860710402800276
|View full text |Cite
|
Sign up to set email alerts
|

Sodium polystyrene sulfonate used to reduce the potassium content of a high‐protein enteral formula: a quantitative analysis

Abstract: The treatment of an enteral formula with sodium polystyrene sulfonate significantly increases its sodium content, with a modest decrease in potassium content. Clinicians using this method in clinical practice should be aware of the increase in sodium content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
3
27
0
2
Order By: Relevance
“…Several studies have demonstrated a reduction in the potassium content of formulas and beverages, such as orange juice, milk, and colas after treatment with SPS. [10][11][12][13][14] However, none have measured its efficacy in treating hyperkalemia in newborns and infants. The purpose of this retrospective study was to evaluate the effect on serum potassium of treating infant formula or EBM with SPS before patient consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a reduction in the potassium content of formulas and beverages, such as orange juice, milk, and colas after treatment with SPS. [10][11][12][13][14] However, none have measured its efficacy in treating hyperkalemia in newborns and infants. The purpose of this retrospective study was to evaluate the effect on serum potassium of treating infant formula or EBM with SPS before patient consumption.…”
Section: Introductionmentioning
confidence: 99%
“…However, there exists possibility that the safety might be related to the inertness of resin. Thanks to the inertness, resin is not decomposed, metabolized in the stomach or absorbed into the body, and is known to be relatively safe (Shepherd et al, 2000;Braunlin et al, 2004;Rivard et al, 2004;Barker et al, 2006). For example, the single-dose LD 50 of sodium polystyrene sulfonate is greater than 8 g/kg in rats, with a TD 10 of 4 g/kg/day (720 g/kg/26 weeks) over 6 months.…”
Section: Toxicitymentioning
confidence: 99%
“…Resin and resinate have been used for controlled release, physicochemical stabilization, and taste masking in pharmaceutical areas since the early 1950s (Zhang et al, 2000;Akkaramongkolporn et al, 2001;Pongjangyakul et al, 2005). Resinates have been also used in soluble or insoluble pharmaceutical ingredients with daily doses of 9~60 g for adsorption and excretion of inorganic ions or microbials from gastrointestinal tracts (Shepherd et al, 2000;Braunlin et al, 2004;Rivard et al, 2004;Barker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lowering the K + content of food before it is consumed may be a helpful approach to improve the variety of the diet of kidney patients. Towards this goal, large scale ion-exchange column chromatography can be used to remove K + from juices without pulp [15][16][17][18][19][20][21], however this approach has not been utilized to create commercial products.…”
Section: Introductionmentioning
confidence: 99%